2014
DOI: 10.1080/08975353.2014.977672
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Responsibility, Safety, and Trust Through a Dialogical Approach: A Case Study in Couple Therapy for Psychological Abusive Behavior

Abstract: This article reports an analysis of conjoint therapy for psychological intimate partner violence, treated via a dialogical approach. The article reviews current controversies surrounding this treatment modality and its outcome. The dialogical approach is presented as an appropriate method for analyzing and understanding the issue of violence, but it is emphasized that the focus on communication does not involve a return to a systemic perspective on intimate partner violence. Four important dimensions are ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
0
16
0
9
Order By: Relevance
“…Findings from the dialogical analysis also showed that monologue was more present in therapy generally (Keltikangas et al ., ). Dialogical dialogue mostly took place between a therapist and either one of the clients (Vall et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Findings from the dialogical analysis also showed that monologue was more present in therapy generally (Keltikangas et al ., ). Dialogical dialogue mostly took place between a therapist and either one of the clients (Vall et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Another relevant aspect during conversations about abusive behaviour is related to trust. The project findings indicate that the couple might have serious difficulties in trusting each other (Vall et al ., ). Also, the clients’ pattern of communication may present a disrupted pattern in which each tries to impose on the other their view of the situation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These themes also relate to responsibility, safety and trust, which have been considered the main goals of conjoint IPV treatment (Vall et al 2014). To begin with, the theme of loyalty involves setting boundaries, which is a basic task for any new family (Minuchin 1974).…”
Section: Discussionmentioning
confidence: 99%